A novel liquid imidazole-copper (II) complex as a thermal latent curing agent for epoxy resins. (12th September 2019) - Yang, Bo; Mao, Yanyun; Zhang, Yihui; Bian, Guofeng; Zhang, Liying; Wei, Yi; Jiang, Qiuran; Qiu, Yiping; Liu, Wanshuang
Abstract: In this study, 1-cyanoethyl-2-ethyl-4-methylimidazole (1C2E4MI) was modified by copper chloride to improve its thermal latency towards epoxy resins. Unexpected complexation between 1C2E4MI and copper chloride was discovered, and two complexes which included a liquid and a solid were generated. The microanalytical results show that the ligand-metal ratios of these two complexes are 7:1 (liquid) and 1:1 (solid), rather than the theoretical 4:1 ratio. The liquid 1C2E4MI-copper (II) complex (Complex-L) exhibits superior miscibility with epoxy resins, and the resulting epoxy systems show distinctly prolonged pot life at 25 and 60 °C. Curing kinetic study indicates the epoxy system containing Complex-L can be cured using a similar manner like that containing 1C2E4MI. Moreover, the epoxy resin cured with Complex-L has glass transition temperature and tensile properties comparable to that cured with 1C2E4MI. Graphical abstract: Image 105971 Highlights: Unexpected complexation between 1-cyanoethyl-2-ethyl-4-methylimidazole (1C2E4MI) and copper chloride was discovered. The compositions of two 1C2E4MI-copper (II) complexes were characterized. The epoxy system with liquid 1C2E4MI-copper (II) complex showed distinctly prolonged pot life at 25 and 60 °C.